A study on suicidal risks in psychiatric adults. (25th April 2011) - Chattopadhyay, Subhagata; Daneshgar, Farhad
Psychiatric patients often commit suicide during illness. Although the occurrences of suicides could be prevented, yet detection of risks at the early stage of the illness is a difficult task as hardly any warning sign/symptom could be detected. This study addresses this important issue and proposes a methodology to It further argues that together these observations could be useful for early detection of suicidal risks.